The Relationship between Exclusive Breastfeeding and The Incidence of Stunting Toddlers - Tasya Aureliyana; Raden Kince Sakinah (Jurnal Riset Kedokteran, 2022)
Abstract. Stunting is a condition when toddlers have a length or height that is less than their average age. Indonesia is the third country with the highest prevalence in the Southeast Asia region, which is 43.8%. Cemara Wetan Village has the highest prevalence of stunting, which is 34.40% of all villages in Indramayu district. One of the efforts to prevent stunting is by providing adequate nutrition from an early age through exclusive breastfeeding. This study aims to determine the relationship between exclusive breastfeeding and the incidence of stunting under five in Cemara Etan Village, Indramayu Regency. This study uses a quantitative research method with an analytical observational research design with a cross-sectional approach. This study used a breastfeeding questionnaire for mothers of toddlers and secondary data for measuring body mass index of toddlers. The analysis technique uses univariate and bivariate analysis using the chi square test. The results showed that there was a significant relationship between exclusive breastfeeding and the incidence of stunting in children under five in Cemara Wetan Village, Indramayu Regency with (p = 0.012, OR = 0.304).\ Abstrak. Stunting merupakan suatu kondisi pada saat balita memiliki panjang atau tinggi badan yang kurang dibandingkan anak rerata usianya. Indonesia merupakan negara ketiga dengan prevalensi tertinggi di regional Asia Tenggara yaitu sebanyak 43,8%. Desa Cemara Wetan memiliki prevalensi angka stunting tertinggi yaitu 34,40% dari seluruh desa di kabupaten Indramayu. Salah satu usaha pencegahan stunting yaitu dengan pemberian nutrisi adekuat sejak usia dini melalui ASI eksklusif. Penelitian ini bertujuan untuk mengetahui hubungan ASI eksklusif terhadap kejadian balita stunting di Desa Cemara Etan Kabupaten Indramayu. Penelitian ini menggunakan metode penelitian kuantitatif dengan desain penelitian observasonal analitik dengan pendekatan crossectional. Penelitian ini menggunakan kuesioner ASI pada ibu balita dan data sekunder pengukuran indeks massa tubuh balita. Tekhnik analisisnya menggunakan analisis univariat maupun bivariat menggunakan chi square test. Hasil penelitian memperlihatkan bahwa terdapat hubungan signifikan antara pemberian ASI Eksklusif dengan kejadian stunting pada balita di Desa Cemara Wetan Kabupaten Indramayu dengan (p=0,012, OR=0,304).